Marketing Planning PT. Luxury Indah Jaya "Premium Laundry Service" - Edi Suwito; Tantri Yanuar Rahmat Syah; Ketut Sunaryanto (Jurnal Indonesia Sosial Teknologi, 2023)
The presence of a different laundry business service in Indonesia, especially in Jakarta and its surroundings. This business plan offers a special premium laundry service for 4 and 5-star hotels. PT. Luxury Indah Jaya (Luxury Laundry) as a provider of premium laundry services for 4 and 5-star hotels focuses on B2B but still pays attention to the needs of the end user. This marketing plan will be formulated and explained regarding marketing goals and objectives, STP marketing strategy, marketing mix with the NICE approach, sales activities, and calculation of income streams and Investment Feasibility Analysis.